EDUKASI TENTANG PENERAPAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) UNTUK KINERJA PEREKAM MEDIS DI RSU Dr. FERDINAND LUMBAN TOBING SIBOLGA - apriana, ana -; ., Likusman (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Hospital Management Information System (SIMRS) is a communication information technology system that processes and integrates the entire flow of hospital service processes in the form of a network of coordination, reporting and administrative procedures to obtain information appropriately and accurately, and is part of the Health Information System. The purpose of the implementation of this PKM is to determine the effect of the application of the hospital information system (SIMRS) on the performance of medical recorders at Dr. Ferdinand Lumban Tobing Sibolga Hospital, using an analytical observational method with a cross sectional approach. The total population is 38 people, the sampling method is with a total sampling where the entire population is sampled, which is 38 people. PKM Implementation Instrument using a questionnaire. The results of the PKM implementation show that most of the implementation of the hospital information system (SIMRS) is in the good category (68.4%). The performance of medical recorders was included in the good category of 29 respondents (76.3%). It is recommended that the hospital provide a fast internet network for the smooth operation of hospital service activities, especially medical records.